NCOG-30. ADJUVANT VERSUS SALVAGE MANAGEMENT FOR IDH-MUTANT LOW GRADE GLIOMA. (9th November 2020) - Tom, Martin; Park, Deborah; Tewari, Surabhi; Wei, Wei; Chao, Samuel; Yu, Jennifer; Suh, John; Ahluwalia, Manmeet; Peereboom, David; Stevens, Glen; Fallah, Jaleh; Prayson, Richard; et al.
Abstract: PURPOSE: Timing of postoperative treatment in low-grade glioma (LGG) remains controversial. We sought to evaluate outcomes between adjuvant versus salvage management among patients with IDH-mutant molecularly-defined LGG. METHODS: We analyzed a single-institutional database of adults diagnosed with LGG (grade II) with an IDH-mutation and either 1p19q-codeletion (oligodendroglioma) or 1p19q-intact (astrocytoma). Cox multivariable analysis (MVA) accounting for age, sex, and extent-of-resection, was used to compare adjuvant versus salvage approaches on overall survival (OS), progression free survival (PFS), next-intervention free survival (NIFS, defined as intervention subsequent to either adjuvant or salvage treatment), and malignant-transformation free survival (MTFS). Adjuvant treatment was defined as immediate postoperative treatment with radiotherapy (RT) and/or temozolomide (TMZ) prior to progression. Salvage management was defined as postoperative observation followed by surgery or RT and/or TMZ at progression. RESULTS: Of 162 patients with oligodendroglioma, median follow-up was 8.5 years (range, 0.03-25.7). Adjuvant treatment was given to 97 (59.9%) patients, with 65 (40.1%) undergoing a salvage approach. On MVA, adjuvant treatment was not associated with OS, PFS, NIFS, or MTFS (p > 0.05 each). Among 82 patients with astrocytoma, median follow-up was 6.1 years (range, 0.5–25.7), and adjuvant treatment was administered to 41 (50.0%) patients, while 41 (50.0%) received salvage management. On MVA, adjuvant treatment was associated with improved PFS (HR 0.42, 95% CI 0.24-0.73, p < 0.001) and NIFS (HR 0.35, 95% CI 0.18–0.65, p < 0.001), but was not associated with OS or MTFS (p > 0.05 each). CONCLUSIONS: Among grade II, IDH-mutant oligodendrogliomas, initial postoperative observation followed by salvage treatment at progression may be appropriate, as immediate adjuvant therapy was not associated improved outcomes. However, a more individualized postoperative management approach is required for grade II, IDH-mutant astrocytomas, as adjuvant treatment was associated with improved PFS and NIFS, but not OS. Further validation and prospective studies are required.